Erodable dam breaching patterns due to overtopping - Mat Lazin, Nor Ain (2014)
There have been numerous studies on dam breaching that have been carried out for a long time, but this area still needs further investigation. Dams which have failed due to breach mechanism have caused disastrous effects to the downstream area, such as loss of lives, property damages, economic and environmental damages. This is due to the complex process of breaching which involves many factors such as cohesiveness of the embankment material, the height of the dam and the slope of the embankment dam. Hence, the aim of this study was to investigate the breach patterns and breach grows when breaching takes place. Besides, this study is also focused on the breach hydrograph that is produced after the failure of embankment. The embankment dam of 0.1m was tested in 11m length and 0.6m width channel. The equation used to measure the outflow discharge was Q = 8/15 (Cd)(2g)0.5 tan (θ/2) (h)2.5. Different embankment parameters were considered, i.e. the embankment materials (coarse and medium sand), the inflow rates (Q1 = 0.6 m3/s, Q2 = 0.9 m3/s and Q3 = 1.2 m3/s) and the slope of the embankment dam (1V:2H and 1V:3H). Most of the embankment dam tested showed that vertical erosion occurred first until a certain point before lateral action took place. Higher inflow rate produced higher peak outflow and shorter peak time. Besides, higher inflow rate flushed away all the embankment materials towards downstream and formed a wedge shape at the end of the process, as observed from the side view. For different embankment slopes used, the flatter slopes prolonged the erosion process about 7.7 % and also reduced the peak outflow value of about 15.8 %. Different grain sizes of soil were also used in the tests and it proved that the smaller grain size of soil reduced the peak outflow value (6.5%) and prolonged the peak time about 13.3%. Process of dam breach is clearly influenced by the embankment material, the embankment slope and the inflow rate.